PERUBAHAN JUMLAH ALUR KUMPARAN STATOR DAPAT MENINGKATKAN KAPASITAS DAYA KELUARAN GENERATOR SINKRON TIGA PHASA - Wiwik Purwati Widyaningsih (Eksergi, 2016)
Total flow charges may increase the capacity of coils stator generator power output synchrounous three phase. The government has tried to addition of powerhouse center, but has not been able to meet the increasing demand for electricity. In the generator itself to boost its output capacity by changing the number of the slot. Changes affect the number of slots in addition to the capacity building of the three-phase synchronous generator output also affect the power factor (Cos φ) and efficiency . Results of the study showed that the three phase synchronous generator after having the capacity to change  the number of slots increases output power, power factor and efficiency to be better than before the revamped its slot number. Keywords  : Increase Output Power, Change Slot